Proposta de padronização na configuração de pedidos para venda de pulverizadores - Martineli, Lucas Cerutti (2020)
This study aims to present a proposal for standardization in ordering sprayer configurations for the sales area. As a methodology, quali-quantitative data were used from the configurations of the machines' product structure, which were generated according to the sales statistics in an industry of agricultural machines and implements. A retrospective of sales over a period of three years was analyzed, from which an overview of current demand and the real need in relation to the production of components was obtained. Among the conclusions of the study, there is the reallocation of 25% of the amount invested in stock to the spare parts sector and a standardization of the settings that cover the flow of the production schedule for the sprayer assembly line.